Canadian Gallup Poll, May 1987, #521_1 - Gallup Canada (Borealis, 2019)
This Gallup poll seeks the opinions of Canadians, on predominantly social and lifestyle issues. The questions ask opinions on smoking, a potential ban on the sale of tobacco, the Charter of Rights and Freedoms and pollution. There are also questions on other topics of interest such as knowledge of the Northwest passage, religious habits and Canada's involvement in the high tech industry. The respondents were also asked questions so that they could be grouped according to geographic, political and social variables. Topics of interest include: the amount of money spent on food per week; the approval of a ban on cigarette advertisments; the approval of the sale of Dome Petroleum to an American company; attending church; the dangers of pollution; the development race in the high tech industry; the effects of a ban on cigarette advertisments; the effects the Charter will have on protecting rights; the ideal number of kids to have in a family; the influence of religion on everyday life; knowledge about the Canadian Charter of Rights and Freedoms; knowledge of the Northwest Passage; the likelihood that you will be smoking in a year; the quality of food today, compared to the past; the seriousness of pollution; smoking cigarettes in the past week; and supporting a ban on the sale of tobacco. Basic demographic variables are also included.